2022
DOI: 10.48550/arxiv.2203.17237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical description of galactic clusters in Finzi gravity model

Abstract: We exploit a new theory of gravity proposed by Finzi, which gives stronger interaction at large scales, to study the thermodynamic description of galaxy clusters. We employ a statistical model to deduce various thermodynamics equations of state. In addition, we analyze the behavior of clustering parameter in comparison to its standard (Newtonian) counterpart. The general distribution function and its behavior with varying strength of clustering parameter are also studied. The possibility of phase transition is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The implications of these ideas are also consistent with observations. The statistical mechanical study of the structure formation and distribution in the universe has been studied rigorously in [5][6][7][8][9][10]. The authors have employed various modified gravity theories to study the effects of these modifications on the statistical properties of large scale structures in the universe.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of these ideas are also consistent with observations. The statistical mechanical study of the structure formation and distribution in the universe has been studied rigorously in [5][6][7][8][9][10]. The authors have employed various modified gravity theories to study the effects of these modifications on the statistical properties of large scale structures in the universe.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical method can be emplyed to study the mass distribution on the largest possible scale [9]. In recent past there has been a tremendous effort to study the effect of modified gravity theories on the galaxy clustering through statistical and thermodynamic methods [10][11][12][13][14][15][16][17][18][19][20][21][22]. It has been observed that the modified theories of gravity does affect the clustering process through a change in a parameter that is related to the strength of correlation called clustering parameter, originally defined as the ratio of Kinetic to potential energy, b = K/2W .…”
Section: Introductionmentioning
confidence: 99%